Chronic bi-maxillary osteomyelitis caused by Actinomycetes in a patient with severe COVID-19 = Osteomyelitis bi-maxilar crónica causada por Actinomycetes en un paciente con COVID-19 severo - López González, Emmanuel; Vitales Noyola, Marlen; Alvarado Hernández, Diana Lorena; Comas García, Andreu; Muñoz Ruiz, Abraham (2023)
Osteomyelitis is defined as the inflammation of the either medullary, cortical, or cancellous bone, including nerves and blood vessels, causing necrosis and bone sequestrum formation; this condition has become a rare pathology, and odontogenic infections are considered the most frequent causal factor. This case shows a patient with bi-maxillary osteomyelitis caused by Actinomyces spp, which was worsened for severe COVID-19 infection. Patient was submitted at surgery as, amplified total bilateral maxillectomy through the surgical technique Weber-Fergusson, and prolonged use of combination of antibiotics, achieved a good recovery. Two years later follow-up, the patient no show imaging or clinical evidence of the infection of osteomyelitis. The present case shows an interesting relationship between a rare infection and its association with COVID-19.
La osteomielitis se define como la inflamación del hueso medular, cortical o esponjoso, incluyendo nervios y vasos sanguíneos, causando necrosis y formación de secuestro óseo; esta condición es una patología rara, y las infecciones odontogénicas son consideradas como el factor causal más frecuente. En este caso, se muestra un paciente con osteomielitis bi-maxilar causada por Actinomyces spp, la cual empeoró por la infección de COVID-19 severo. El paciente fue sometido a una cirugía, maxilectomía bilateral total amplificada, a través de la técnica quirúrgica de Weber-Fergusson, y el uso prolongado de una combinación de antibióticos, logrando una buena recuperación. A los 2 años de seguimiento, el paciente no mostró evidencia clínica o imagenológica de la infección de osteomielitis. El presente caso muestra una interesante relación entre una infección rara y su asociación con COVID-19.
En revista Odóvtos, vol. 25, no.3 (septiembre-diciembre 2023)
Descripción basada en el contenido visto el 16 de enero, 2025
También disponible en formato HTML y EPUB